Fluid flow and heat transfer around mechanical seals - Barnes, N. D. (Cranfield University, 1990)
Mechanical seals are used extensively on rotary applications where the sealed fluid is under pressure. They may rightly be considered to be generally reliable and trouble free, many giving lives of over 3 years. However, a significant number, particularly on arduous and often critical duties, exhibit apparently random mid-life failure characteristics which cannot be easily explained. Of these "random" failures, the largest proportion appear to be attributable to overheating due to loss of the vital interface fluid film. The mechanism of interface film loss depends on a large number of interrelated variables and a substantial amount of work has been carried out over many years to attempt to alleviate the problem. Little work however has been reported on the nature of the fluid flow around the seal; this is determined by seal chamber geometry and affects the removal of potentially deleterious heat, vapour or gases, and solids. At present, many seals are required to run in "stuffing boxes" - cavities designed for soft packing rather than mechanical seals. The aim of this project has been to study the flow behaviour in these stuffing boxes and a number of novel chamber designs. The techniques involved using transparent housings and direct measurements of convective heat transfer coefficients. Significant improvements over existing designs were achieved using a housing flared at 45° away from the seal and this design forms the basis of recommendations for improved seal systems. This design was tested under simulated field conditions described in a Design Study and Case Study and found to be successful. The recommendations are backed up by a mathematical model of turbulence viscosity which seeks to explain some of the complex structured flows observed. A corollary to the thesis explains how the results of this work will form a major input to improved international standards.